Drosophila Strip serves as a platform for early endosome organization during axon elongation. - Sakuma, C.; Kawauchi, T.; Haraguchi, S.; Shikanai, M.; Yamaguchi, Y.; Gelfand, V.I.; Luo, L.; Miura, M.; Chihara, T. (Nature communications, 2014)
Early endosomes are essential for regulating cell signalling and controlling the amount of cell surface molecules during neuronal morphogenesis. Early endosomes undergo retrograde transport (clustering) before their homotypic fusion. Small GTPase Rab5 is known to promote early endosomal fusion, but the mechanism linking the transport/clustering with Rab5 activity is unclear. Here we show that Drosophila Strip is a key regulator for neuronal morphogenesis. Strip knockdown disturbs the early endosome clustering, and Rab5-positive early endosomes become smaller and scattered. Strip genetically and biochemically interacts with both Glued (the regulator of dynein-dependent transport) and Sprint (the guanine nucleotide exchange factor for Rab5), suggesting that Strip is a molecular linker between retrograde transport and Rab5 activation. Overexpression of an active form of Rab5 in strip-mutant neurons suppresses the axon elongation defects. Thus, Strip acts as a molecular platform for the early endosome organization that has important roles in neuronal morphogenesis.